Broad anti-SARS-CoV-2 antibody immunity induced by heterologous ChAdOx1/mRNA-1273 vaccination - Kaku, Chengzi I; Champney, Elizabeth R; Normark, Johan; Garcia, Marina; Johnson, Carl E; Ahlm, Clas; Christ, Wanda; Sakharkar, Mrunal; Ackerman, Margaret E; Klingström, Jonas; Forsell, Mattias N E; Walker, Laura M (Science (American Association for the Advancement of Science), 2022)
Heterologous prime-boost immunization strategies have the potential to augment COVID-19 vaccine efficacy. We longitudinally profiled severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S)-specific serological and memory B cell (MBC) responses in individuals who received either homologous (ChAdOx1:ChAdOx1) or heterologous (ChAdOx1:mRNA-1273) prime-boost vaccination. Heterologous messenger RNA (mRNA) booster immunization induced higher serum neutralizing antibody and MBC responses against SARS-CoV-2 variants of concern (VOCs) compared with that of homologous ChAdOx1 boosting. Specificity mapping of circulating B cells revealed that mRNA-1273 boost immunofocused ChAdOx1-primed responses onto epitopes expressed on prefusion-stabilized S. Monoclonal antibodies isolated from mRNA-1273-boosted participants displayed overall higher binding affinities and increased breadth of reactivity against VOCs relative to those isolated from ChAdOx1-boosted individuals. Overall, the results provide molecular insight into the enhanced quality of the B cell response induced after heterologous mRNA booster vaccination.